Use of a smart electrically assisted bicycle (VELIS) in the health field -Proof of concept-. (July 2020) - Rey-Barth, S; Eychenne, C; Rolland, C; Pinsault, N; Bosson, JL
Highlights: We confirm that riding an E-bike should be considered as physical activity. The engine brake of the VELIS ensures the safety of users, even novices in any situation. Recordings show that it took between 1 and 3 min for the novice to become familiar with the VELIS and to get optimal assistance. This pilot study confirms that VELIS is an accessible, intuitive and secure tool for PA, whatever the level of training in healthy subjects. Abstract: Physical activity (PA) is highly recommended in the management of most chronic diseases. For these patients, the smart electric bicycle can be effective to improve adherence to this behavior. The E-bike used in this study (called VELIS) has an innovative onboard technology that allows for subject monitoring and the engine power is designed to adapt to the user's abilities. A prerequisite for the use of the VELIS with patients is to initially carry out a pilot study on healthy subjects. The objective was to evaluate the impact of the customizable settings on physiological parameters and to ensure this prototype's efficiency and safety of use. Twelve healthy participants with various profiles (physical condition, used to cycling or not) were included. They have completed four times a 14 km itinerary with various settings of the VELIS. We recorded GPS data, heart rate and perceived exertion. Based on exercise intensity, we confirm that riding an E-bike should be considered as a physical activity. Safety of the participants is ensured by the engine brake. Recordings show that it took between 1 and 3 min for the novice to become familiar with the VELIS and to get optimal assistance. The main finding of this pilot study confirms that VELIS is an easy to use and secure tool to make PA approachable, whatever the level of training in healthy subjects.